A prospective analysis of smoking and human papillomavirus infection among men in the HPV in Men Study. Issue 10 (13th November 2013) - Schabath, Matthew B.; Villa, Luisa L.; Lin, Hui‐Yi; Fulp, William J.; Lazcano‐Ponce, Eduardo; Salmerón, Jorge; Abrahamsen, Martha E.; Papenfuss, Mary R.; Quiterio, Manuel; Giuliano, Anna R.
<x xml:space="preserve">Abstract</x> At present it is unknown whether the higher prevalence of human papillomavirus (HPV) infection among smokers in men is attributed to a higher probability of acquiring an infection or because of longer infection persistence. Thus, we investigated the role of smoking on the incidence (acquisition) and clearance (persistence) of genital HPV infections among 4, 026 men in the HPV in Men (HIM) Study, a multinational prospective study of the natural history of genital HPV infection in men. Genital HPV infections were grouped by any, oncogenic and nononcogenic HPV infections and smoking status was categorized as current, former and never smokers. The incidence of any, oncogenic and nononcogenic HPV infections was significantly higher among current smokers compared to former and never smokers (p < 0.01). In multivariable analyses adjusting for sexual behavior and potential confounders, when compared to never smokers, current smokers exhibited significantly higher probability of acquiring any [hazard ratio (HR) = 1.23; 95% confidence interval (CI) 1.02–1.50] and nononcogenic (HR = 1.21; 95% CI 1.00–1.45) infections and a borderline significant probability for oncogenic infections (HR = 1.18; 95% CI 0.98–1.41). Although the median duration of HPV infection was generally longer among current smokers, we found no statistically significant associations in the multivariable analyses. Overall, these results demonstrated that current smoking exhibited the highest incidence and highest probability of acquiring genital HPV infections.